Training Factors Within the Ontario Manufacturing Sector - LeBrasseur, Rolland; Lambert, Marie-Josee (Relations industrielles / Industrial Relations, 1991)
Through on-site and supported training, business in Canada has a crucial role to play in the supply of specialized and multiskilled workers. The results of a survey of the Ontario manufacturing sector are presented, and intra- and extraorganizational factors influencing the training activities of firms are identified. On average, employees received 2.6 days of directly provided training and some supported training. It is concluded that improvement in training participation rates has taken place throughout the 1980s and that leading companies are reaching new levels in the duration of training offered. A variety of factors, such as management commitment, are found to be significant predictors of training activities.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Employees; Improvements; Labor Unions; Manufacturers; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Statistical data; Surveys; Training; Variables